Dendritic cell sphingosine-1-phosphate lyase regulates thymic egress - Zamora-Pineda, Jesus (J Exp Med, 2016)
T cell egress from the thymus is essential for adaptive immunity and involves chemotaxis along a sphingosine-1-phosphate (S1P) gradient. Pericytes at the corticomedullary junction produce the S1P egress signal, whereas thymic parenchymal S1P levels are kept low through S1P lyase (SPL)–mediated metabolism. Although SPL is robustly expressed in thymic epithelial cells (TECs), in this study, we show that deleting SPL in CD11c(+) dendritic cells (DCs), rather than TECs or other stromal cells, disrupts the S1P gradient, preventing egress. Adoptive transfer of peripheral wild-type DCs rescued the egress phenotype of DC-specific SPL knockout mice. These studies identify DCs as metabolic gatekeepers of thymic egress. Combined with their role as mediators of central tolerance, DCs are thus poised to provide homeostatic regulation of thymic export.